The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d2ma00095d
|View full text |Cite
|
Sign up to set email alerts
|

Enabling fine-grain free 2-micron thick CISe/CIGSe film fabrication via a non-hydrazine based solution processing route

Abstract: Solution processing of CuInSe2/CuInGaSe2 (CISe/CIGSe) photovoltaic devices from a non-hydrazine based routes have been studied for the past few years and a significant improvement in device performance has been achieved...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 39 publications
3
29
0
Order By: Relevance
“…Although the amine-thiol solvent system can dissolve metal selenides and selenium, the thiol is still present to potentially act as a sulfur. 36 Depending on subsequent annealing conditions, the formation of sulfoselenide materials rather than selenides can occur. 37 While in some cases sulfur alloying into a metal selenide material is beneficial, in other cases the pure selenide material is desired.…”
Section: Introductionmentioning
confidence: 99%
“…Although the amine-thiol solvent system can dissolve metal selenides and selenium, the thiol is still present to potentially act as a sulfur. 36 Depending on subsequent annealing conditions, the formation of sulfoselenide materials rather than selenides can occur. 37 While in some cases sulfur alloying into a metal selenide material is beneficial, in other cases the pure selenide material is desired.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the surface morphology of CIGS to the n-buffer layer determines the formation of carrier recombination that should be avoided. 19,116,[128][129][130][131][132] This journal is © The Royal Society of Chemistry 2023 Therefore, good crystallinity and surface morphology of the CIGS layer could enhance the performance of the solar cell because of minimum carrier recombination formation. 127…”
Section: Quaternary Cigs-or Czts-based Solar Cellsmentioning
confidence: 99%
“…(d) Summary of PCEs of single-junction quaternary-CuCh-based solar cells with and without CdS layers 19,[130][131][132]…”
mentioning
confidence: 99%
“…Thus, developing a scalable deposition technique in ambient air is critically important for this technique to be applied to mature industrial processes. Among the scalable deposition techniques such as spray pyrolysis, [18,19] inkjetprinting, [20,21] and doctor-blading, [22][23][24][25] doctor-blading is the most simple and easy-control one that is compatible with high throughput roll-to-roll fabrication. However, unlike perovskite [26,27] and organic thin-film solar cells [28,29] for which doctorblading has been extensively used and high performance has been realized, fabrication of chalcopyrite absorber through doctor-blading is relatively rare.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of CISSe solar cell fabricated by doctor‐blading molecular precursor solution has been 6.7%, which was reported by Tiwari [ 24 ] group in 2005. We note that while our work was under review process, an article was published by Agrawal [ 25 ] group, which reported 12.9% CISSe and 14.1% CIGSSe solar cells with the absorbers blade‐coated from amine–thiol‐based solutions with interface modification.…”
Section: Introductionmentioning
confidence: 99%